Inventaire d'aides dans les environnements multimédias d'apprentissage et propositions d'aides multimodales - Laurence Hamon (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Starting from the hypothesis that multimodality has a role to play in help offers, this article gives an analysis of help guides on offer within a corpus of CD-Roms and web sites which aim to teach French as a foreign language. Then, based on the results of this analysis, a certain number of multimodal help guides produced within the framework of the Amalia module are shown and described before being tested by learners of French as a foreign language.